The Effects of Self-regulation on Self-discipline of Primary Education Grade 4 Students - Rodjanadid, Kassama; Chanvirat, Waradee (Ratchaphruek Journal, 2023)
The purposes of this experimental research were to: 1) Compare the students’ self-discipline between the experimental group and control group before and after learning; and 2) Compare the self-discipline between the experimental group and the control group. The sample in this study were the fifty-five students who were selected by cluster sampling and voluntarily participate; 30 for the experimental group and 25 for the control group. Research instrument used in the experiment were the 11 Self-Regulation Program time, 1 hours at the time, and the questionnaire. Data were analyzed by mean, standard deviation, and t-test. The results showed that: After the experiment, the experimental group students have self-discipline scores higher than before the experiment, and than the control group with a statistically significance at the .01 level.